The promise of the nation gender, history, and nationalism in contemporary Ilokano literature - Galam, Roderick G. (Ateneo de Manila University Press, 2008)
"The Promise of the Nation examines the construction of the nation in contemporary Ilokano literature in the intersections of gender, history, and nationalism by tracing Ilokano literature's political, material and socio-cultural connections and examining its intervention in Philippine socio-political discourse, history, and historiography. It attends to and addresses the limitations, contradictions and potential constituting Ilokano writers' efforts to (re)make a Filipino nation, efforts made in the context of Spanish and American imperialism, neocolonialism, martial law, militarization, urban squatting, patriarchy, migrant work, and the marginalization of ethnic peoples. Finally, the book argues that the writers' project of realizing what Caroline Hau has evocatively called the nation's "promise of community" may be more powerfully imagined and grasped were nationalism transformed by feminism; indeed if we dream this nation, see and seek its promise and possibility with a feminist-communitarian imagination.